Peran Mahasiswa Program Asistensi Mengajar dalam Mengembangkan Kreativitas Anak Usia Dini: Studi Kasus di TK Hang Tuah Bengkulu - Fidhia Andani; Dinda Aulia; Fatimah Azzahra; Annisa Sofiah Akram; Hirlita Anggrayani; Fenti Nurhaliza (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to examine the role of teaching assistance program students in developing the creativity of early childhood at Hang Tuah Kindergarten in Bengkulu. Children's creativity is an important aspect that supports cognitive, language, motor, social, and emotional development. The study used a qualitative approach with a case study method. The research subjects included teaching assistance students, classroom teachers, and early childhood children aged 4–6 years. Data were collected through observation, interviews, and documentation. The results showed that students acted as facilitators of creative learning through storytelling, educational games, art activities, and motor activities. The children appeared more enthusiastic, imaginative, and demonstrated problem-solving skills. In addition, students also contributed to non-learning activities such as ceremonies, drum band competitions, and administration, which supported the formation of children's character and discipline. In conclusion, teaching assistance program students play a significant role as companions and agents of innovation who are able to create a fun and meaningful learning atmosphere for early childhood.